Analisis Bahan Ajar Maharah Qira’ah di SMP Muhammadiyah 3 Yogyakarta Berbasis CEFR - Alimudin, Alimudin; Dania, Itmamu; Saputri Hidayat, Adelia Ayu (UIR Press, 2023)
This study aims to analyze the teaching materials of Arabic maharah qira'ah in class IX of SMP Muhammadiyah 3 Yogyakarta. This research is a library research (literature study). In this study, there are two data sources used, namely primary and secondary data sources. The primary data source is taken from the book Arabic Language Education SMP Muhamamdiyah Class IX by Anji Fathunaja, S.Pd.I. and Sugeng Riyanyo, S.Pd.I. published by the Muhammadiyah Central Leadership Agency in 2018 Primary and Secondary Education and European Language Learning Outcomes Standards (CEFR). While secondary data sources are books, journal articles, and sites that discuss the analysis of teaching materials for maharah qira'ah as well as references that support this research. The data analysis technique uses descriptive analysis techniques. After the data obtained then describes systematically the results of the research. The results of the research on the analysis of Arabic maharah qira'ah teaching materials in class IX SMP Muhammadiyah 3 Yogyakarta, state that the Arabic Language Education Book SMP Muhammadiyah 3 Yogyakarta has been arranged systematically and interestingly, so it is suitable to be used as a textbook in Arabic language learning and more specifically in maharah qira'ah, because the book has presented materials related to students' spiritual attitudes and knowledge. In addition, the materials presented are in accordance with the CEFR-based learning outcome standards, and if referring to the CEFR standards, they are included in the A2/ Elementary and B1/Intermediate levels.